Effects of HAR1 on cognitive function in mice and the regulatory network of HAR1 determined by RNA sequencing and applied bioinformatics analysis - Zhang, Luting; Lin, Shengmou; Huang, Kailing; Chen, Allen; Li, Nan; Shen, Shuhan; Zheng, Zhouxia; Shi, Xiaoshun; Sun, Jimei; Kong, Jingyin; Chen, Min (Frontiers in Genetics, 2023)
Background: HAR1 is a 118 bp segment that lies in a pair of novel non-coding RNA genes. It shows a dramatic accelerated change with an estimated 18 substitutions in the human lineage since the human-chimpanzee ancestor, compared with the expected 0.27 substitutions based on the slow rate of change in this region in other amniotes. Mutations of HAR1 lead to a different HAR1 secondary structure in humans compared to that in chimpanzees. Methods: We cloned HAR1 into the EF-1α promoter vector to generate transgenic mice. Morris water maze tests and step-down passive avoidance tests were conducted to observe the changes in memory and cognitive ability of mice. RNA-seq analysis was performed to identify differentially expressed genes (DEGs) between the experimental and control groups. Systematic bioinformatic analysis was used to confirm the pathways and functions that the DEGs were involved in. Results: Transgenic mice’s memory and cognitive ability were significantly improved. Results of gene ontology (GO) analysis showed that cerebral cortex development was the most significantly enriched GO term related to HAR1 in brain development. The DEGs enriched in this term included Lhx2, Emx2, Foxg1, Nr2e1, and Emx1. These genes all play an important role in regulating the functioning of Cajal–Retzius cells (CRs). The DEGs were also enriched in glutamatergic synapses, synapses, memory, and the positive regulation of long-term synaptic potentiation. In addition, "Cellular response to calcium ions" exhibited the highest Rich factor in the GO analysis. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of the DEGs showed that the neuroactive ligand-receptor interaction pathway was the most significantly enriched pathway, with DEGs notably enriched in neuroactive ligand-receptor interaction, axon guidance, and cholinergic synapses. Conclusions: HAR1 overexpression led to improvements in the transgenic mice’s memory and cognitive abilities. The possible mechanism for this was that the long non-coding RNA (lncRNA) HAR1A affected brain development by regulating the function of CRs. Moreover, HAR1A may be involved in ligand-receptor interaction, axon guidance, and synapse formation, all of which are important in brain development and evolution. Furthermore, cellular response to calcium may play an important role in those processes.